The Effectiveness of Direct Learning Model in Science Learning for Grade IV at SDN Sindangbarang 03 - Rohfi Hestuti; Kuntoro Kuntoro (UM Purwokerto Press, 2025)
The effectiveness of implementing the Direct learning model in science learning at SDN Sindangbarang 03 has not been explored in depth. Understanding how this model is implemented, how students respond to and understand the science material delivered through this model, and the challenges and opportunities faced by teachers in its implementation. This study aims to understand the effectiveness of the Direct learning model in learning Natural and Social Sciences (IPAS) in grade IV of SDN Sindangbarang 03. This study uses a case study approach to explore students' learning experiences and teachers' perspectives related to the implementation of the Direct learning model in the subject of Science. The focus of the study includes teacher strategies, student involvement, conceptual understanding. Data collection was carried out through participatory observation, semi-structured interviews with grade IV teachers, and focus group discussions (FGD) with students. The collected data were analyzed qualitatively through the processes of transcription, reduction, categorization, and interpretation. The results of the study are expected to provide comprehensive insights into the contribution of the Direct learning model to students' understanding and interest in science subjects more effectively.